Static Transfer Switch Applied to Single-Phase Uninterruptible Power Supply - Maia Rodrigues, Marcus Vinicius; Silva, Newton da; Serrao Goncalves, Flavio Alessandro [UNESP]; Batschauer, A. L.; Filho, AJS; Rech, C.; Brandao, D. I.; Martins, D. C.; Tedeschi, E.; Santos, E. C.; Marafao, F. P.; Antunes, FLM; et al. (Ieee, 2019)
This paper presents a Static Transfer Switch (STS) applied to Single-Phase Uninterruptible Power Supply. The performance of two STS topologies was evaluated, one traditional composed of thyristors and the other formed by the association of IGBTs and diodes. In addition, two approaches for detection of disturbances in the grid voltage waveform are explored: the first method is based on the dq0 transformation and the second one is performed through a PLL (Phase Locked Loop) algorithm. Simulation and experimental results were performed to evaluate the performance of topologies and methods for disturbances detection.
Keywords: Static Transfer Switch; IGBT; UPS; Passive Standby